ADHD in Early Childhood: Part 2 - Information for Preschool Teachers - Heidi Liss Radunovich; Allie Munch (EDIS)
Instructing children with ADHD can be a difficult task for many teachers, especially for those in the childcare or preschool setting. Children with ADHD are often identified because they show problem behaviors in preschool. Early childhood educators should be aware of ADHD symptoms so that they can spot the signs of the disorder. This 3-page fact sheet was written by Heidi Liss Radunovich and Allie Munch, and published by the UF Department of Family, Youth and Community Sciences, July 2012.